Outcome of Supraglenoid Tubercle Fractures in 12 Dogs - Kulendra, Elvin R.; Beer, Andrew J. C.; Hockley, George C. A.; Goh, Derniese; Lafuente, Pilar; Perry, Karen L. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to report the outcome and complications of surgical stabilization following fracture of the supraglenoid tubercle in dogs.Materials and Methods Data from three referral centres (Queen Mother Hospital for Animals, Michigan State University and Veterinary Referral Hospital Hallam) were reviewed retrospectively for cases of supraglenoid tubercle fracture (n = 12).Results Overall success rate was 9/12. Major complication rate was 2/12 and minor complication rate was 9/12. All fractures that had major complications were comminuted. Methods of stabilization included pin and tension band wire (n = 5), lag screw (n = 2), plate fixation (n = 2), fragment removal (n = 2) and conservative management (n = 1).Clinical Significance Good outcomes can be achieved following fractures of the supraglenoid tubercle, although cases with comminution have a higher complication rate. Further research into the optimal method of fixation and postoperative management is required.
Keywords: fracture; scapula; supraglenoid tubercle; dog